2, 4, 9‐Triazaadamantanes with "Clickable" Groups: Synthesis, Structure and Applications as Tripodal Platforms. Issue 43 (18th August 2020) - Semakin, Artem N.; Nelyubina, Yulia V.; Ioffe, Sema L.; Sukhorukov, Alexey Yu.
Abstract : 2, 4, 9‐Triazaadamantanes (TRIADs) are promising yet scarcely available, conformationally rigid platforms for potential applications in the design of functional molecules and materials. Here, we report a facile synthesis of various N ‐ and C7‐substituted 2, 4, 9‐triazaadamantanes, starting from amines and 4‐allylhepta‐1, 6‐dienes. A focus was placed on the synthesis of 2, 4, 9‐triazaadamantanes bearing reactive groups (NH2, propargyl, OH) on the bridge nitrogen atoms, which were then used to decorate the 3D scaffold by hydrazone, triazole, and boronate linkages. A reversible opening of the adamantane cage to the acyclic tris‐oxime form was observed for 2, 4, 9‐triazaadamantanes possessing hydroxy‐groups on the nitrogen atoms (TRIAD‐triols). This process could be controlled by temperature or by complexation of TRIAD‐triol with a boronic acid. The structure of 2, 4, 9‐triazaadamantanes and the stereodynamics at the bridge nitrogen atoms were studied by X‐ray analysis and DFT calculations. Abstract : 2, 4, 9‐Triazaadamantanes (TRIADs) are a poorly investigated class of hetrocage molecules, which have the potential for applications as synthetic platforms. Here, comprehensive studies on the synthesis, structure and stability of TRIADs were performed. Facile modification of bridge N ‐positions in TRIADs through different click‐strategies demonstrates the versatile characteristics of this new 3D scaffold.